Integrating Mindful, Meaningful, and Joyful Learning to Enhance Student Engagement and Learning Outcomes in Economic Education - Amjad Salong; Paisal Ansiska (STAI Hubbulwathan Duri, 2025)
The shift toward student-centered learning in higher education demands pedagogical strategies that enhance engagement, motivation, and deep learning. This study explores the effectiveness of an integrative instructional approach—Mindful, Meaningful, and Joyful Learning (MMJ)—in improving student engagement and outcomes in an Economic Learning Strategy course. A quasi-experimental design with a nonequivalent control group was used. Eighty-four undergraduate students were divided evenly into MMJ (experimental) and conventional (control) groups. Over four sessions, the MMJ group experienced learning activities incorporating mindfulness, real-world relevance, and joyful interaction. Data were collected through engagement observations, ARCS-based motivation surveys, project-based assessments, and a SWOT analysis. Statistical analysis included t-tests and effect size measurements. Students in the MMJ group demonstrated significantly higher levels of cognitive (M = 4.4), affective (M = 4.6), and behavioral engagement (M = 4.5) compared to the control group. Motivation scores were also superior across ARCS dimensions: attention (M = 4.7), relevance (4.6), confidence (4.8), and satisfaction (4.5). Learning outcomes in the MMJ group surpassed the control group in concept understanding (M = 4.6), originality (4.5), relevance (4.7), and argumentation (4.4). The findings affirm MMJ’s potential to enhance learning experiences through integrated, student-centered instruction. A SWOT analysis informed five strategic recommendations for broader implementation, including hybrid models and gamification. MMJ offers a viable framework for transforming higher education into a more engaging, reflective, and meaningful experience.